2019
DOI: 10.1093/humrep/dez117
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploid rescue precedes X-chromosome inactivation and increases the incidence of its skewness by reducing the size of the embryonic progenitor cell pool

Abstract: STUDY QUESTION Do monosomy rescue (MR) and trisomy rescue (TR) in preimplantation human embryos affect other developmental processes, such as X-chromosome inactivation (XCI)? SUMMARY ANSWER Aneuploid rescue precedes XCI and increases the incidence of XCI skewness by reducing the size of the embryonic progenitor cell pools. WHAT IS KNOWN ALREADY More than half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…We demonstrated that the XCI ratios of KS patients followed a normal distribution. Furthermore, the frequencies of skewed XCI and extremely skewed XCI in KS patients were comparable to previous data obtained from healthy young women [7]. These findings are consistent with previous reports by Zitzmann et al [15] and Zinn et al [16], which documented apparently random XCI in KS patients.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We demonstrated that the XCI ratios of KS patients followed a normal distribution. Furthermore, the frequencies of skewed XCI and extremely skewed XCI in KS patients were comparable to previous data obtained from healthy young women [7]. These findings are consistent with previous reports by Zitzmann et al [15] and Zinn et al [16], which documented apparently random XCI in KS patients.…”
Section: Discussionsupporting
confidence: 92%
“…The XCI ratios of the two cases were 13.3%:86.7% and 91.6%:8.4%. The frequencies of skewed XCI and extremely skewed XCI in the KS cohort were comparable to those in healthy young women [7] (11.1% vs. 11.5%, p = 0.641 and 5.6% vs. 1.9%, p = 0.342, respectively).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations